2009
DOI: 10.1111/j.1365-2141.2009.07595.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with sirolimus results in complete responses in patients with autoimmune lymphoproliferative syndrome

Abstract: Summary We hypothesized that sirolimus, an mTOR inhibitor, may be effective in patients with autoimmune lymphoproliferative syndrome (ALPS) and treated patients who were intolerant to or failed other therapies. Four patients were treated for autoimmune cytopenias; all had a rapid complete or near complete response. Two patients were treated for autoimmune arthritis and colitis, demonstrating marked improvement. Three patients had complete resolution of lymphadenopathy and splenomegaly and all patients had a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
122
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(128 citation statements)
references
References 14 publications
3
122
0
3
Order By: Relevance
“…Although MMF has been demonstrated to lead to measurable improvements in autoimmune disease and is well tolerated, MMF does not induce lymphocyte death nor has it been demonstrated to have any effect on lymphoproliferative disease or the reduction of DNTs. 1,5 As a result, some ALPS patients treated with MMF alone may have PRs and/or eventual relapse. Moreover, the subjects in our series either failed (N 5 3) or had a PR (N 5 4) to MMF, prompting a need for alternative, steroid-sparing therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although MMF has been demonstrated to lead to measurable improvements in autoimmune disease and is well tolerated, MMF does not induce lymphocyte death nor has it been demonstrated to have any effect on lymphoproliferative disease or the reduction of DNTs. 1,5 As a result, some ALPS patients treated with MMF alone may have PRs and/or eventual relapse. Moreover, the subjects in our series either failed (N 5 3) or had a PR (N 5 4) to MMF, prompting a need for alternative, steroid-sparing therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that treatment with the mammalian target of rapamycin inhibitor, sirolimus (Rapamune) led to a complete response (CR) in a small retrospective cohort of 5 children with corticosteroid refractory ALPS. 5 Based on that study, we opened a prospective multi-institutional clinical trial (#NCT00392951) using sirolimus for children with treatmentrefractory ALPS. After we found an early efficacy signal, we broadened the inclusion criteria to any child with autoimmune cytopenias who failed or was intolerant to standard immunosuppressive therapy (corticosteroids and/or IV immunoglobulin G [IVIgG]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though sirolimus can cause mild thrombocytopenia, it is active against immunemediated thrombocytopenia and is under clinical investigation for this indication. [66,67] Rarer side effects include peripheral edema, interstitial pneumonitis, and renal insufficiency. Edema and pneumonitis are more common in adults and with combination regimens.…”
Section: Rapalogsmentioning
confidence: 99%
“…In general, the ALPS phenotype and ALPS type III were enrolled in our studies more recently than the ALPS type Ia patients; therefore, the younger somatic patients in these groups were more likely to benefit from recent recommendations in management, emphasizing avoidance of splenectomy. 32,33 Patients with somatic FAS mutations who were originally classified as ALPS type III were all male and had a later age of onset of disease with the exception of two 1-year olds. This could be the result of the small number of patients studied, and evaluation of additional patients may yield a more balanced gender ratio, similar to the somatic type Ia patients originally classified as ALPS phenotype, with 3 males and 3 females.…”
Section: Somatic Fas Mutations In Alps 5167mentioning
confidence: 99%